Evaluación de varios sustratos orgánicos en el crecimiento de la lombriz roja californiana (Eisenia foetida) alimentadas con estiércol de bovino, pollinaza y compost, en la zona de Babahoyo. - Aviles Gómez, Sandy Elizabeth (2018)
VIII. SUMMARY The present experimental work was carried out near the classrooms of the School of Agricultural Engineering of the Faculty of Agricultural Sciences of the Technical University of Babahoyo, located at kilometer 7 ½ of the Babahoyo-Montalvo road. The geographic coordinates are 9 801,116 UTM south latitude and 668,673 UTM west longitude and 8 msnm. The zone presents a humid tropical climate, with average annual temperature of 25.7ºC, an average annual precipitation of 1845 mm, relative humidity of 76% and 804.7 hours of annual average heliophany. It was used as genetic material, Californian worm (Eisenia foetida) the objectives were: Identify the most appropriate substrate to increase the population density of the California red worm (Eisenia foetida), know the most appropriate density that generates the highest yield of humus and compost and economically analyze the treatments. The treatments studied were different substrates such as Fermented cattle manure (EBF); Compost with bovine manure (CEB); Compost with chicken manure (CEP); Fermented cattle manure (EBF) and compost with bovine manure (CEP); Fermented cattle manure (EBF) and compost with chicken manure (CEP); Fermented cattle manure (EBF) plus compost with bovine manure (CEB) and compost with chicken manure (CEP). The experimental design called "Complete random blocks" (DBCA) with six treatments and four repetitions was used. All the variables evaluated were subjected to the analysis of variance and to determine the different statistics among the means of the treatments, the Tukey statistical significance test was used at the 0.05 level. The beds had dimensions of 0.7 m long x 0.5 m wide, a drawer height of 0.3 m, with distance of 1 m between drawer units and 1 m between repetitions. During the development of the trial, the following tasks were performed, such as manure collection and solarization, preparation of bovine compost and poultry litter, bed construction, earthworm planting, bed maintenance, bed watering and earthworm feeding. In order to estimate the effects of the treatments, data were taken on density, weight, worm length, bed temperature, worm production, humus yield and economic analysis. Based on the results obtained, it was concluded that Fermented cattle manure (EBF) was the treatment with the highest population density; the greatest weight of earthworm was obtained with the treatment Fermented cattle manure (EBF) and compost with bovine manure (CEP); with Fermented cattle manure (EBF) a greater average in worm length was obtained; for the temperature no significant differences were observed, this was due to the fact that all the beds were protected with the same type of material, worm production stood out with the use of Fermented cattle manure (EBF); the highest humus yield was obtained with Fermented cattle manure (EBF) and compost with bovine manure (CEP) and net profit of $ 65.48. Keywords.- organic substrate, california earthworm, manure, compost.